2019
DOI: 10.1093/jb/mvz076
|View full text |Cite
|
Sign up to set email alerts
|

CRY2 suppresses trophoblast migration and invasion in recurrent spontaneous abortion

Abstract: Disruption of circadian rhythms is associated with aberrant trophoblast migration and invasion in recurrent spontaneous abortion (RSA). This study aims to explore the functional role and the mechanisms of cryptochrome 2 (CRY2), a fundamental component of the circadian clock, in regulating trophoblast migration and invasion. Human extravillous trophoblast cell line HTR-8/SVneo was used as a cell model. Cell migration and invasion were examined using wound healing assay and Transwell assay, respectively. The mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Urokinase plasminogen activator (uPA) has been shown to involve in cell mobility (Blasi & Sidenius, 2010;Tang, Hill, Brumwell, Chapman, & Wei, 2008), therefore, more studies are needed to prove in the future. The Boyden chamber system was generally used to determine the effects of TET on cell migration and invasion in vitro (Wu, Cheng, Liu, Jiang, & Yang, 2019). Thus, we used this method to show that TET at 1-10 μM after 24 hr treatment significantly suppressed the cell migration and invasion of NPC-TW 039 cells in dose-dependently (Figure 3a,b).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Urokinase plasminogen activator (uPA) has been shown to involve in cell mobility (Blasi & Sidenius, 2010;Tang, Hill, Brumwell, Chapman, & Wei, 2008), therefore, more studies are needed to prove in the future. The Boyden chamber system was generally used to determine the effects of TET on cell migration and invasion in vitro (Wu, Cheng, Liu, Jiang, & Yang, 2019). Thus, we used this method to show that TET at 1-10 μM after 24 hr treatment significantly suppressed the cell migration and invasion of NPC-TW 039 cells in dose-dependently (Figure 3a,b).…”
Section: Discussionmentioning
confidence: 98%
“…The Boyden chamber system was generally used to determine the effects of TET on cell migration and invasion in vitro (Wu, Cheng, Liu, Jiang, & Yang, 2019). Thus, we used this method to show that TET at 1–10 μM after 24 hr treatment significantly suppressed the cell migration and invasion of NPC‐TW 039 cells in dose‐dependently (Figure 3a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant CRY2 expression suppresses proliferation and invasion of extravillous trophoblast cells, preventing normal placentation. 32 This suggests that clock gene system in the uterus plays an important role in the maintenance of pregnancy. To support the above speculation, our preliminary data demonstrated that uterine Bmal1-deficient mice failed to maintain a successful pregnancy (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Another group reported that cryptochrome 2 (CRY2), a transcriptional repressor that forms a core component of the circadian clock, is irregularly overexpressed in villous specimens obtained from women with recurrent spontaneous abortion. Aberrant CRY2 expression suppresses proliferation and invasion of extravillous trophoblast cells, preventing normal placentation 32 . This suggests that clock gene system in the uterus plays an important role in the maintenance of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the EVTs invade the maternal uterus, which allows the placenta to be fixed to the uterine wall, and results in the maternal spiral artery being reshaped to provide nutrition for the developing fetus. Errors at any step in this process can lead to placenta-related pathological pregnancies, including RSA (Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%